2018
DOI: 10.1111/hae.13623
|View full text |Cite
|
Sign up to set email alerts
|

Ranges and drivers of risk associated with sports and recreational activities in people with haemophilia: results of the Activity‐Intensity‐Risk Consensus Survey of US physical therapists

Abstract: Introduction Limited evidence describes physical activity‐associated bleeding risks for people with haemophilia, and risks are usually described only generically. Aim To assess activity‐specific ranges of risk for joint, soft tissue and head bleeds by identifying inherent and modifiable risk factors associated with each activity, based on opinions of expert physical therapists (PTs). Methods Physical therapists from US haemophilia treatment centres (HTCs) participated in a survey of 101 physical activities. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The recently published Activity-Intensity-Risk Consensus Survey engaged HTC-based physical therapists to identify the range and drivers of risk of bleeding in 102 athletic activities. The results of the survey informed discussion guides that can be used by HTC team members to help patients with hemophilia identify activities that are safe and will enable them to maintain an active lifestyle 18. The results of the current study suggest that a similar evaluation of intimate activities would greatly benefit the hemophilia community.…”
Section: Discussionmentioning
confidence: 73%
“…The recently published Activity-Intensity-Risk Consensus Survey engaged HTC-based physical therapists to identify the range and drivers of risk of bleeding in 102 athletic activities. The results of the survey informed discussion guides that can be used by HTC team members to help patients with hemophilia identify activities that are safe and will enable them to maintain an active lifestyle 18. The results of the current study suggest that a similar evaluation of intimate activities would greatly benefit the hemophilia community.…”
Section: Discussionmentioning
confidence: 73%
“…In our study, interviewed sports physicians thought that boxing is to be avoided, in agreement with previously published opinions. A survey on physical therapists reported that risks for hemophilia patients inherent to a sport included impacts with surface/ball/equipment [33]. The choice of a suitable sport may require specific medical counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from anecdotal experiences and biomechanical considerations, there are few data to inform guidelines either in the general sense or for patients with particular target joints. However, the recent approach taken in the Activity Intensity Risk initiative through survey/consensus of 17 expert physiotherapists to evaluate range of risk and risk drivers of 101 physical activities could be extended to evaluate sexual positions 15 …”
Section: Discussionmentioning
confidence: 99%
“…However, the recent approach taken in the Activity Intensity Risk initiative through survey/consensus of 17 expert physiotherapists to evaluate range of risk and risk drivers of 101 physical activities could be extended to evaluate sexual positions. 15 It is important to note that an increasing number of middle-aged PWH experience erectile dysfunction (ED). 3,5 In addition to discussing the psychosocial issues related to sexuality, HCPs could also evaluate PWH for ED using a single question from the Massachusetts Male Aging Study: 'How often are you able to get and keep an erection good enough for sexual intercourse -always, usually, sometimes or never?…”
Section: Discussionmentioning
confidence: 99%